1991
DOI: 10.3109/00016349109007157
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of adenomyosis uteri in a Greek population

Abstract: The reported incidence of adenomyosis based on unselected hysterectomies varies so widely that conclusions regarding the influence of any factor on that incidence are difficult to reach, although the relation of adenomyosis uteri to endometrial carcinoma has been the subject of only a few studies. In a 5-year period at the General Hospital of Athens, 646 hysterectomies were performed. All data were retrieved from the surgical pathology laboratory files concerning adenomyosis uteri with either simultaneous endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Histology, depth of MI, tumor grade, presence of LVSI, positive peritoneal cytology, tumor size and LNS have been universally recognized as prognostic factors for determining long-term clinical course of the disease (25,26). Although certain studies have evaluated the association between AM and the clinical course of EEC, the mechanism by which AM interferes with tumoral progression remains unresolved (9,12,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Histology, depth of MI, tumor grade, presence of LVSI, positive peritoneal cytology, tumor size and LNS have been universally recognized as prognostic factors for determining long-term clinical course of the disease (25,26). Although certain studies have evaluated the association between AM and the clinical course of EEC, the mechanism by which AM interferes with tumoral progression remains unresolved (9,12,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of adenomyosis among women who undergo hysterectomy has varied from 8% to 28% in studies conducted in Greece, Italy, Denmark, and the United States, and has been reported to be as high as 57% in Pakistan. (Bergholt, Eriksen, Berendt, Jacobsen, & Hertz, 2001; Chrysostomou et al, 1991; Curtis, Hillis, Marchbanks, & Peterson, 2002; McCausland, 1992; Parazzini et al, 1997; Shaikh & Khan, 1990; Vavilis et al, 1997; Vercellini et al, 1995; Vercellini et al, 2006) Variability in these estimates is partially due to differences in histological criteria used for diagnosis and may also be related to differences in the relative frequency of comorbidities that necessitate hysterectomy in different populations. (Bergholt et al, 2001)…”
Section: Introductionmentioning
confidence: 99%
“…In hysterectomy specimens the incidence of adenomyosis reported in the literature varies, ranging from a high of 61.5% to a low of 8.8% (2,5,(11)(12)(13)(14)(15). Hyperestrogenemia, a cause of endometrial hyperplasia and fibroid growth, has been associated with adenomyosis, (5,11) as has prior pregnancy (2,3,13,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…When present, these symptoms lead to a presumptive preoperative diagnosis of adenomyosis, and are often used as an indication for hysterectomy. While some have suggested that adenomyosis is associated with these symptoms (1)(2)(3)(4)(5)(20)(21)(22) and more commonly coexists with fibroids (2) and endometriosis (2,(17)(18)(19) others have concluded the opposite view (3,(11)(12)(13)(14)(15)(16). It is apparent that these issues need further clarification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation